The Phytotoxin Coronatine Contributes to Pathogen Fitness and Is Required for Suppression of Salicylic Acid Accumulation in Tomato Inoculated with Pseudomonas syringae pv. tomato DC3000 - Srinivasa Rao Uppalapati; Yasuhiro Ishiga; Tamding Wangdi; Barbara N. Kunkel; Ajith Anand; Kirankumar S. Mysore; Carol L. Bender (Molecular Plant-Microbe Interactions, 2007)
The roles of the phytotoxin coronatine (COR) and salicylic acid (SA)-mediated defenses in the interaction of Pseudomonas syringae pv. tomato DC3000 and tomato (Solanum lycopersicum) were investigated. Unlike findings reported for Arabidopsis thaliana, DC3000 mutants impaired for production of COR or one of its components, coronafacic acid (CFA) or coronamic acid (CMA), induced distinctly different disease lesion phenotypes in tomato. Tomato plants inoculated with the CFA- CMA- mutant DB29 showed elevated transcript levels of SlICS, which encodes isochorismate synthase, an enzyme involved in SA biosynthesis in S. lycopersicum. Furthermore, expression of genes encoding SA-mediated defense proteins were elevated in DB29-inoculated plants compared with plants inoculated with DC3000, suggesting that COR suppresses SlICS-mediated SA responses. Sequence analysis of SlICS revealed that it encodes a protein that is 55 and 59.6% identical to the A. thaliana ICS-encoded proteins AtICS1 and AtICS2, respectively. Tomato plants silenced for SlICS were hypersusceptible to DC3000 and accumulated lower levels of SA after infection with DC3000 compared with inoculated wild-type tomato plants. Unlike what has been shown for A. thaliana, the COR- mutant DB29 was impaired for persistence in SlICS-silenced tomato plants; thus, COR has additional roles in virulence that are SA independent and important in the latter stages of disease development. In summary, the infection assays, metabolic profiling, and gene expression results described in this study indicate that the intact COR molecule is required for both suppression of SA-mediated defense responses and full disease symptom development in tomato.